PENGARUH PEMBERIAN KOMPOS Calopogonium mucunoides dan JARAK TANAM TERHADAP PERTUMBUHAN DAN HASIL KEDELAI (Glycine max (L). Merril) - Neneng Nur Khodijah; Aslim Rasyad (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2018)
The objective of this research was to look for the alternative fertilizer suitable to be used for soybean grown under different plant spacing. This research was established in the Agricultural Experimental Station, Agriculture Faculty, University of Riau from August to December 2016. The field experiment was arranged in randomized completely block design with three replication. Three planting spaces were used including J1: 40 cm x 12 cm, J2: 40 cm x 15 cm, and J3: 40 cm x 20 cm. The second factor was Collopogonium mucoides (CM) compos as alternative fertilizer including; P1: inorganic N, P, K fertilizer with recommended rate, P2: CM compost fertilizers 2500 kg/ha, and P3: CM compost fertilizers 5000 kg/ha. Parameters observed were plant height, internodes length, flowering date, harvesting date, filled pod percentage, number of seeds per plant, seed weight per plant, yield per m2, and 100-seed weight. Analysis of variance was performed to the data and the mean differences were specified by the least significant difference test at 5% level. The result showed that applying CM compost to soybean resulted better performance compare to inorganic fertilizer. Increasing the rate of CM compost from 2500 kg to 5000 kg per ha tent to increase filled pods percentate, number of seeds per plant, grain yield per m2 and 100 seeds weight. In term of planting space, wider planting space resulted low density of plants per area and produced greater filled pods percentage, greater seed number, higher seed weight per plant, higher grain yield per m2 and greater 100-seed weight. Keywords: Collopogonium, compost, plant spacing, growth and soybean yield